Relationship between arm span and height in postmenopausal osteoporotic women - AKYÜZ, GÜLSEREN DERYA (SPRINGER HEIDELBERG, 2008)
Osteoporosis is a progressive systemic skeletal disease characterized by low bone density and microarchitectural deterioration of the bone. A minimum 3-cm difference between arm span and height makes up one of the criteria for suspecting osteoporosis. Therefore, it is easy to determine osteoporotic women by measuring the proportion of height to the arm span. The purposes of this study are to assess the relationship between arm span and height and to compare them in postmenopausal and young healthy women. This was a randomized-controlled, prospective study. There were two groups in this study. Group I included 70 postmenopausal osteoporotic women and group II had 70 healthy young women. Height, weight and arm span of the individuals were measured in all subjects. Bone mineral density and radiological examination of spine were also evaluated. Mean age of postmenopausal women was 64.4 +/- 8.6 years and it was 27.3 +/- 3.5 years in young healthy women. Mean height was 152 +/- 5.1 and 161.5 +/- 5.9 cm in group I and II, respectively. Mean arm span length was 159.6 +/- 6.3 cm in postmenopausal women and 163.5 +/- 6 cm in young healthy women. Mean arm span-height difference was significantly higher in postmenopausal women when compared to healthy young women (7.7 +/- 3.6 and 2 +/- 2.9 cm, respectively, P < 0.001). We suggest that arm span measurements can be used in the estimation of youth height and age-related loss in stature in postmenopausal women.
Keywords: arm span; height; osteoporosis; vertebral fracture; VERTEBRAL FRACTURES; BONE MASS; DEFORMITY; MEN